2004
DOI: 10.1897/02-512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to a combination of zinc‐ and lead‐spiked sediments on mouthpart development and growth in Chironomus tentans

Abstract: Exposures to either zinc or lead in contaminated sediments have been shown to induce characteristic deformities in larval chironomids. This study examined the effects of exposure to lead and zinc in combination on Chironomus tentans larvae. Proportions of mouthpart deformities in populations of larvae reared in sediments containing nominal combinations of lead and zinc were tested for additive, synergistic, and antagonistic interactions using logistic regression. Metal body burdens, body size measurements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
(48 reference statements)
0
22
0
1
Order By: Relevance
“…Disorders in the functions of organism of insects, which inhabited an environment contaminated with zinc, such as Pterostichus oblongopunctatus, Poecilus cupreus, were observed by Bisthoven et al (1992), Martinez et al (2001Martinez et al ( , 2002Martinez et al ( , 2004, Maryanski et al (2002), Lagisz (2008). Consumption of zinc-contaminated food by insects caused delays in their development, for example, among larvae of Aglais urticae (Linnaeus, 1758) (Lindqvist, 1994), Trichoplusia ni (Hubner, 1800-1803) (Larsen et al, 1994), P. oblongopunctatus (Zygmunt et al, 2006) and Issoria lathonia (Linnaeus, 1758) (Noret et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Disorders in the functions of organism of insects, which inhabited an environment contaminated with zinc, such as Pterostichus oblongopunctatus, Poecilus cupreus, were observed by Bisthoven et al (1992), Martinez et al (2001Martinez et al ( , 2002Martinez et al ( , 2004, Maryanski et al (2002), Lagisz (2008). Consumption of zinc-contaminated food by insects caused delays in their development, for example, among larvae of Aglais urticae (Linnaeus, 1758) (Lindqvist, 1994), Trichoplusia ni (Hubner, 1800-1803) (Larsen et al, 1994), P. oblongopunctatus (Zygmunt et al, 2006) and Issoria lathonia (Linnaeus, 1758) (Noret et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Developmental diseases of the embryo, among which are neural tube defects (Brender et al, 2006), have been related to the exposure to heavy and semi-heavy metals, as shown mostly in animal models (Lopez et al, 2008;Martinez et al, 2004;Robinson et al, 2009Robinson et al, , 2010. Sources of exposure to metals include industry, the home environment, health behavior and nutritional and dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…When they exceed threshold concentrations they can have very harmful effects on individual organisms, populations, communities and ecosystems. In aquatic ecosystems heavy metals can influence invertebrate development (Martinez et al 2004), abundance and structure of the population (Gower et al 2006), as well as influencing invertebrate morphology (Martinez et al 2009) and some genetic and physiological systems (Florea, Büsselberg 2006;Michailova et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%